Implementation Of The E-Invoice System To Support Efficiency In Value Added Tax (VAT) Reporting At Perum Bulog Banyumas - Steyna Luknafa Hakim; Dona Primasari; Siti Maghfiroh (Journal of Innovative and Creativity, 2026)
The implementation of the E-Invoice system by the Directorate General of Taxes (DGT) represents a strategic innovation in Indonesia’s tax administration reform, aimed at enhancing transparency, efficiency, and accuracy in tax reporting. This study aims to analyze the effectiveness of E-Invoice implementation in improving the efficiency of Value Added Tax (VAT) reporting at Perum BULOG Banyumas. The research employs a qualitative descriptive method through a field study conducted during an internship period. Data were collected through direct observation, in-depth interviews, and documentation of tax administration processes. The findings indicate that the E-Invoice system significantly improves tax reporting efficiency by reducing processing time, enhancing data accuracy, and promoting greater transparency in transactions. Nevertheless, several challenges remain, including unstable internet connectivity, limited human resources proficient in digital systems, and the need for continuous training. This study is expected to serve as a reference for other state-owned enterprises (SOEs) in optimizing E-Invoice implementation to enhance compliance and administrative efficiency in the digital taxation era..